2017
DOI: 10.1253/circj.cj-17-0554
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Long-Term Use of Tolvaptan in Patients With Heart Failure and Chronic Kidney Disease

Abstract: Background:We assessed the long-term safety and efficacy of tolvaptan in 102 patients with heart failure (HF) and chronic kidney disease (CKD). Median follow-up duration was 1.6 years (1.0-4.4 years). Methods and Results:One patient discontinued tolvaptan because of hypernatremia. There were no changes in renal function or electrolytes during the 1-year follow-up. The cardiac-related death-free or HF-related hospitalization-free survival rate was significantly higher in patients receiving tolvaptan than in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…The primary endpoint of this study was rehospitalization due to worsening HF, and the secondary endpoints Kaplan-Meier analysis revealed that the incidence of rehospitalization was significantly lower in the TLV (+) group than in the TLV (−) group (log-rank test; p = 0.018) ( Figure 2). As shown in 18,19 In our study, 82.8% of the patients started TLV therapy from the first day of hospitalization, and TLV therapy reduced loop diuretics doses both at discharge and after 6 months, and it also prevented WRF development until 6 months…”
Section: Echocardiographysupporting
confidence: 68%
“…The primary endpoint of this study was rehospitalization due to worsening HF, and the secondary endpoints Kaplan-Meier analysis revealed that the incidence of rehospitalization was significantly lower in the TLV (+) group than in the TLV (−) group (log-rank test; p = 0.018) ( Figure 2). As shown in 18,19 In our study, 82.8% of the patients started TLV therapy from the first day of hospitalization, and TLV therapy reduced loop diuretics doses both at discharge and after 6 months, and it also prevented WRF development until 6 months…”
Section: Echocardiographysupporting
confidence: 68%
“…_ 1 ) T D $ F I G ] renal function is a key to better prognosis in HF patients. Table 2 summarizes the results of six long-term tolvaptan therapy studies, including four Japanese ones [27,[31][32][33][34]. Tolvaptan dose ranges were 4.9-9.8 mg/day in four Japanese studies, whereas two studies in other countries were performed at 30 mg/day [20,35].…”
Section: Renal Functionmentioning
confidence: 99%
“…However, those were reports on the short‐term use of TLV. Studies on the long‐term use of TLV reported a decrease in the rate of re‐hospitalization due to cardiac failure and fewer instances of renal function worsening . TLV therapy was also reported to be more effective in maintaining renal function than increasing the dose of loop diuretics .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported on the efficacy of TLV in patients with CKD and heart failure . Furthermore, in recent years, it has been reported that long‐term administration of TLV in the management of heart failure suppressed re‐hospitalization rates and also decreased the worsening of renal function . In heart failure complicated with advanced CKD, repeated hospitalization for heart failure is one of the main reasons for initiating dialysis.…”
mentioning
confidence: 99%